Spitfire the illustrated biography - Glancey, Jonathan (Atlantic Books, 2006)
Presented in a large format, this illustrated book presents a celebration of a great British invention, of the men and women who flew it and supported its development, and of the industry that manufactured both the aircraft and the Rolls-Royce engines that powered them.